Development and validation of the knowledge and attitude regarding childhood vaccination (KACV) questionnaire among healthcare workers: the Malay version - Azidah Abdul Kadir; Norhayati Mohd Noor; Ahmad Faiq Mukhtar (Taylor & Francis Group, 2021)
Health care workers play an important role in supporting childhood vaccination as they are the most trusted source of vaccine-related information for parents. However, there is limited validated tools to measure their knowledge and attitude on childhood vaccination. This study aims to develop and validate knowledge and attitude regarding childhood vaccination (KACV) questionnaire among healthcare workers. The questionnaire was developed based on literature reviews and underwent a sequential validation process, including content, face validity and exploratory factor analysis. However, the attitude section is unidimensional and has undergone reliability analysis only. The preliminary knowledge questionnaire contains 33 items and the attitude questionnaire consists of 17 items. The preliminary KACV showed a high item Content Validity Index and Face Validity Index. The final questionnaire consists of 10 items for knowledge and 15 items for attitude. The Cronbach alpha for the knowledge and attitude section were 0.896 and 0.861, respectively. KACV is a valid and reliable tool to measure healthcare workers' knowledge and attitude on childhood vaccination.